BELI SEKARANG, BAYAR NANTI: PERANGKAP ATAU PELUANG? ANALISIS PENGGUNAAN PAY-LATTER DI E-COMMERCE SHOPEE - Sriyono Sriyono; Denata Putri Marlinton; Rizqi Qurrota A'Yun Burhanuddin (Ensiklopedia of Journal, 2023)
The development of online shopping has influenced payment methods previously known only as cash payments, paper payments, and card payments have been affected by the growth of internet purchases and are now implemented into new electronic payment systems. Online credit payment is available via pay-latter. Using Pay-latter can make it easier for customers to shop through technology. Therefore, this writing aims to evaluate the trigger of problems or the impact that occurs on the use of pay-latter on Shopee e-commerce. The systematic literature review (SLR) method was applied in this study. Utilizing certain related writing statements, the SLR approach is used to find, examine, assess, and interpret all existing research on the subjectof events of interest. The results showed that changes in people's social life today are increasingly complex. However, pay-latter services from e-commerce platforms continue to increase the purchasing power of young people. There is a correlation between purchasing power-related services with a high correlation value and Pay-latter services have a positive and negative effect on purchasing power in e-commerce